Treatment of Prolactinomas in Low-Income Countries - Ivan Kruljac; Lora Stanka Kirigin; Mateja Strinović; Jelena Marinković; Hrvoje Ivan Pećina; Vatroslav Čerina; Darko Stipić; Milan Vrkljan (International Journal of Endocrinology)
Purpose. In low-income countries, prolactinomas are difficult to manage with dopamine agonists (DA). We compared the effectiveness of DA in microprolactinomas as a first line treatment and as adjuvant therapy for residual macroprolactinomas treated surgically. Methods. Our retrospective study analyzed 78 patients, 38 with microprolactinomas and 40 with macroprolactinomas. Microprolactinomas were treated with DA. Macroprolactinomas were treated with microsurgical or endoscopic adenomectomies and adjuvant DA. Surgical remission was defined as normoprolactinemia three months postoperatively, and long-term remission as normoprolactinemia at the last control. Results. Surgical remission was achieved in 9 patients (23%). Postsurgical tumor mass was reduced by 50% (34–68). Residual macroprolactinoma size was greater than microprolactinoma size prior to treatment (10 mm versus 4 mm, P<0.001). Both groups received similar doses of DA. Long-term remission occurred in 68% of microprolactinomas and 43% of macroprolactinomas (P=0.102). Prolactin (PRL) levels at the last control were similar in both groups (23.1 versus 32.9 mcg/L, P=0.347). Conclusion. Comparable remission rates and PRL levels were reached in microprolactinomas and macroprolactinomas using similar doses of DA. Although complete tumor resection is the goal of surgery, our study suggests that even partial surgical removal has a role in treatment of prolactinomas since it may enhance the response to DA.